Kant's Dialectic of Enlightenment. - Ramsauer, Laurenz (European Journal of Philosophy, 2026)
Kant's moral thought emphasizes both our ability to make adequate, immediate moral judgment, as well as our deep‐seated forms of self‐entrapment. Strikingly, these forms of self‐entrapment are not simply the result of reason being overpowered by forces external to it, but arise out of reason itself, as pathological versions of otherwise genuine ideals of reason. Two such pathologies are false versions of the moments of Kant's enlightenment ideal. Kant's enlightenment ideal encompasses both thinking for oneself and thinking in community with others; in their pathological versions, these moments of the enlightenment ideal become the delusion of full control over one's epistemic situation through "logical egoism" and the delegation of responsibility by choosing "immaturity" vis‐à‐vis external authority. Because these pathologies of reason easily drop out of view, interpretations of Kant's enlightenment project frequently obscure the challenge of avoiding them and underestimate the difficulty of making progress toward enlightenment. In this article, I discuss both the pathologies of reason and Kant's own implicit resolution: the capacity for healthy forms of trust. Together, the two moments of enlightenment, their respective pathologies, and healthy forms of trust constitute the original dialectic of enlightenment.